THE EFFECT OF COVARIANCE AND CORRELATION AMONG SECURITIES IN A PORTFOLIO AND PORTFOLIO RISK REDUCTION - Yusuf, Muhamad
The risk of a portfolio can be minimized by increasing the number of securities held in the portfolio. Some studies concluded that risk, as measured by the standard deviation of return and the number of securities held in a portfolio are inversely proportional. However, there are some limitations to this approach. First, an investor can only hold a limited amount of securities before it becomes unmanageable and not economically viable. Second, the rate of risk reduction diminishes quickly as portfolio size increases due to the nature of the relationship and therefore further increase in portfolio size will only bring minor risk reduction. In order to reduce risk while maintaining the size of the portfolio, a new approach will be needed. This paper will examine the relationship between the covariance and correlation among portfolio components and risk by using multiple linear regression, with risk as the dependent variable and covariance and correlation as the independent variable. The findings of this paper suggest that there is a relationship between risk and correlation and covariance of portfolio components. It implies that risk reduction can be achieved without increasing portfolio size by appropriately matching the correlation and covariance of the securities in a portfolio.